2011
DOI: 10.4238/vol10-2gmr1104
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic study and barcoding of the blood cockle, Tegillarca granosa, found on the west coast of peninsular Malaysia using the COI gene

Abstract: ABSTRACT. Blood cockles are among the most economically important brackish water invertebrates found in Malaysia. However, our knowledge of blood cockle phylogeny and systematics is rudimentary, especially for the species Tegillarca granosa. It is unclear, for instance, whether the cockles occurring on the west coast of peninsular Malaysia constitute a single species, or multiple, phylogenetically distinct species. We performed the first DNA molecular phylogenetic analysis of T. granosa to distinguish it from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The star-like shape of the TCS network and the shallow length of branches (the maximum distance between the ancestor haplotype and the most divergent haplotype corresponds to only seven nucleotides) would suggest a recent population expansion (Clement et al, 2000). As a point of comparison, haplotype diversity of A. tuberculosa from the NSMT was higher (36.7 vs 28.5%) than the genetic diversity reported for the same species extracted from Nariño region (Colombia) by Chamorro & Rosero (2016) or from Anadara granosa from Malaysia (14.7%) (Chee et al, 2011b). Figure 2.…”
Section: Geneticsmentioning
confidence: 86%
“…The star-like shape of the TCS network and the shallow length of branches (the maximum distance between the ancestor haplotype and the most divergent haplotype corresponds to only seven nucleotides) would suggest a recent population expansion (Clement et al, 2000). As a point of comparison, haplotype diversity of A. tuberculosa from the NSMT was higher (36.7 vs 28.5%) than the genetic diversity reported for the same species extracted from Nariño region (Colombia) by Chamorro & Rosero (2016) or from Anadara granosa from Malaysia (14.7%) (Chee et al, 2011b). Figure 2.…”
Section: Geneticsmentioning
confidence: 86%
“…studies on its phylogenetic status are limited in the literature especially the phylogenetics status in Indonesia. In the previous study reported by [18], reported only Malaysian T. granosa were phylogenetically and DNA Barcoding studied. [19], compared the phylogenetic status of Bivalvia, but also only include the T. granosa from South Korea.…”
Section: Discussionmentioning
confidence: 99%